Water Quality and Quantity Issues for Turfgrasses in Urban Landscapes - Beard, James B.; Kenna, Michael P. (Council for Agricultural Science and Technology (CAST), 2008)
Scientists have documented an array of benefits to the environment and to humans resulting from turfgrasses. Water management is a key component of healthy turfgrasses, and it directly affects nutrient use efficiency and plant productivity. This Special Publication, which follows from a 2006 workshop, presents the best current science for the efficient use of water for turfgrasses in urban landscapes, including considerations for low-precipitation landscapes, water quality protection, water use policies, pesticide leaching, nutrient transport in surface runoff, water requirements, cultural practices, and irrigation systems. An evaluation of these issues is critical for determining future research needs and public policy decisions.
Keywords: Water Quality; Turfgrass Management; Urban Landscape